Pyrodinium bahamense var. compressum and other dinoflagellate cyst distribution in surface sediments along the coasts of Tacloban City in San Pedro Bay, Leyte, Philippines - Abia, Chelsea Mae S.
A baseline study of the abundance of dinoflagellate cysts in surface sediments of Inner San Pedro Bay, Leyte, Philippines is presented in this paper. Sediment samples were collected from eleven stations in the study area on March 2015. Determination of the occurrence of dinoflagellate cysts was followed by the identification to the lowest possible taxonomic level. Dinoflagellate cyst densities were determined and expressed as cysts per gram of dry weight (cysts g-1 DW). Dinoflagellate cyst taxa were sparse with relatively low occurrence and were sporadically distributed in relatively low densities in all sampling stations of the study area. A total of six cyst species from six stations were found and identified to be members of three dinoflagellate groups: Gonyaulacoid, Gymnodinoid, and Protoperidinoid. No cysts of P. bahamense var. compressum were detected. Cell density only had an average of >1 cysts g -1. Factors such as organic content, dry bulk density of sediments, as well as depth affected cyst distribution and density in Inner San Pedro Bay, Leyte.